A Mastery Learning Capstone Course to Teach and Assess Components of Three Entrustable Professional Activities to Graduating Medical Students. Issue 2 (15th March 2019) - Salzman, David H.; McGaghie, William C.; Caprio, Timothy W.; Hufmeyer, Kathryn K.; Issa, Nabil; Cohen, Elaine R.; Wayne, Diane B.
Abstract: Problem: Thirteen measurable Entrustable Professional Activities (EPAs) have been proposed by the Association of American Medical Colleges as a means to operationalize medical school graduates' patient care qualifications. Mastery learning is an effective method for boosting clinical skills, but its applicability to the EPAs remains to be studied. The authors designed this study to evaluate a mastery learning intervention to teach and assess components of 3 of the 13 EPAs in a 4th-year capstone course. Intervention: The course featured mastery learning principles and addressed three EPA-based skills: (a) obtain informed consent, (b) develop a differential diagnosis and write admission orders, and (c) write discharge prescriptions. All students underwent a baseline skills assessment, received feedback, engaged in deliberate practice with actionable feedback, and completed a similar skills-based posttest assessment. Students continued with practice and testing until the minimum passing standards (MPSs) were reached for each posttest. Context: All medical students at a single medical school (Northwestern University, Feinberg School of Medicine) who matriculated in 2012 and graduated with the class of 2016 participated in a required transition to residency course immediately prior to graduation. Outcome: There were 134 students eligible to participate, and 130 (97.0%) completed all curricular requirements and assessments. All 130 medical students who completed the course met or exceeded the MPS for each of the three EPA-based clinical skills. Reliability coefficients for outcome data were uniformly high. Measures for each of the three clinical skills showed statistically significant improvement. Lessons Learned: The capstone course was an effective approach to teach and assess components of three EPA-based clinical skills to mastery learning standards in a 4th-year capstone course. We learned that this approach for implementation is feasible and results in significant improvement in components of EPA skill performance. Next steps will include developing assessments incorporating the mastery model into components of additional EPAs, identifying the best location within the curriculum to insert this content, and expanding the number of assessments as part of a larger assessment system.